Maharah dan Kafa’ah Dalam Pembelajaran Bahasa Arab - Miftachul Taubah (Universitas Yudharta Pasuruan, 2019)
Arabic in learning has four language skills that must be mastered by students, namely listening skills (mahÄrah al-istimÄâ€™), speaking skills (mahÄrah al-kalÄm), reading (mahÄrah al-qirÄ'ah) and writing skills (mahÄrah al- kitÄbah). This conceptual study discusses the genius learning strategy in writing skill learning (mahÄrah al-kitÄbah). The genius learning strategy is a learning strategy that involves the mental and all cognitive structures of students and reconstructs and raises student experiences that have been experienced through visual, auditory, and kinesthetic student learning modalities, so that students' experiences emerge through visual, auditory and kinesthetic media. Genius learning strategies fall into the category of meaningful learning theories.